Pembuktian Okun’s Law dalam Pertumbuhan Ekonomi di Indonesia - Pasaribu, Esti (Convergence: The Journal of Economic Development, 2022)
This study aims to investigate the impact of economic growth and inflation on unemployment in Indonesia over the period 1990-2021. Okun's Law states that there is a relationship between economic growth and unemployment, where the percentage increase in economic growth will be offset by a greater change in the unemployment rate. In other side, the classical Philips curve indicates a trade-off between inflation and unemployment. The data used in this study are secondary data of economic growth, unemployment rate, and inflation rate in Indonesia, obtained from Central Bureau of Statistics and Bank Indonesia website. The data was processed using the autoregressive distribution lag model (ARDL)  to obtain the regression coefficients. Aggregated data results show a negative relationship between economic growth and inflation to the unemployment rate. Thus, the authorities must focus on sustaining economic growth and inflation to reduce the unemployment rate in Indonesia.   Keywords :  Economic Growth1, Unemployment Rate2, Inflation 3